Stone recurrence among Indonesian kidney stone formers: a comprehensive analysis of genetic polymorphism, demographic, and clinical factors - Atmoko, Widi; Savira, Missy; Fajriani, Rosalina; Wistara, Sevita Sathya; Asmarinah; Harahap, Alida Roswita; Witjaksono, Fiastuti; Werdhani, Retno Asti; Safriadi, Ferry; Hamid, Agus Rizal Ardy Hariandy; Birowo, Ponco; Rasyid, Nur; Taher, Akmal (Faculty of Medicine Universitas Indonesia, 2024)
BACKGROUND The recurrence rate of kidney stone disease (KSD) can exceed 50% within 5 years. This study aimed to investigate factors associated with stone recurrence based on single nucleotide polymorphisms (SNPs) of the calcium-sensing receptor (CaSR) rs1801725 and rs1042636, demographic, and clinical profiles. METHODS We collected data on the demographic and clinical characteristics of 80 adult kidney stone formers from April 2021 to September 2022, including peripheral blood samples, morning and 24-hour urine, and 7-day water intake records. Real-time polymerase chain reaction was used to evaluate SNP. Comparisons were made between patients with recurrent and first-time stones. RESULTS 41% of 80 patients have experienced stone recurrence. Recurrent stone formers exhibited significantly higher 24-hour urine calcium excretion (p = 0.03) and lower serum calcium levels (p = 0.019) than first-time stone formers. Hypocitraturia (100%), low urine volume (78%), and hyperoxaluria (55%) were the main abnormalities of all patients. No significant differences were found in CaSR gene polymorphisms and other demographic, biochemical, or clinical parameters. CONCLUSIONS Recurrent stone formers had higher 24-hour urine calcium excretion and lower serum calcium levels. Other risk factors and CaSR polymorphisms may insignificantly affect KSD recurrence.